2017
DOI: 10.1089/jmf.2016.3860
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Moringa oleifera Decreases Hepatic Adiposity and Ameliorates Glucose Intolerance in High-Fat Diet-Induced Obese Mice

Abstract: Metabolic diseases, such as glucose intolerance and nonalcoholic fatty-liver disease (NAFLD), are primary risk factors for life-threatening conditions such as diabetes, heart attack, stroke, and hepatic cancer. Extracts from the tropical tree Moringa oleifera show antidiabetic, antioxidant, anti-inflammatory, and anticancer effects. Fermentation can further improve the safety and nutritional value of certain foods. We investigated the efficacy of fermented M. oleifera extract (FM) against high-fat diet (HFD)-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…To determine the effect of melatonin on HF diet‐fed mice, body weight, liver, and subcutaneous adipose tissue were weighed (Figure A‐D). As expected, HF diet significantly increased the body weight ( P < 0.05) and relative weight of subcutaneous adipose tissue to body weight in mice ( P < 0.001) . Melatonin treatment tended to alleviate HF‐induced weight gain, but the difference was insignificant ( P > 0.05).…”
Section: Resultssupporting
confidence: 53%
“…To determine the effect of melatonin on HF diet‐fed mice, body weight, liver, and subcutaneous adipose tissue were weighed (Figure A‐D). As expected, HF diet significantly increased the body weight ( P < 0.05) and relative weight of subcutaneous adipose tissue to body weight in mice ( P < 0.001) . Melatonin treatment tended to alleviate HF‐induced weight gain, but the difference was insignificant ( P > 0.05).…”
Section: Resultssupporting
confidence: 53%
“…In addition, quercetin may have been involved in the reduction of the inflammatory process by inhibiting the action of neutral factor kappa-beta (NF-kβ) and subsequent NF-kB-dependent downstream events and inflammation [ 80 ]. Further, fermentation of MO appears to enhance the anti-inflammatory properties of MO [ 81 ]. C57BL/6 mice, fed for 10 weeks with distilled water, fermented and non-fermented MO [ 81 ].…”
Section: Effects Of Moringa Oleifera On the Prementioning
confidence: 99%
“…Further, fermentation of MO appears to enhance the anti-inflammatory properties of MO [ 81 ]. C57BL/6 mice, fed for 10 weeks with distilled water, fermented and non-fermented MO [ 81 ]. Investigators reported decreases in the mRNA levels of inflammatory cytokines and reductions in endoplasmic reticulum stress in those animals fed the fermented product.…”
Section: Effects Of Moringa Oleifera On the Prementioning
confidence: 99%
“…MO roots showed evidence of restraint against IL‐2 activity (Sashidara et al, ). Fermentation of MO decreased hepatic adiposity, endoplasmic reticulum anxiety and improved resistance to glucose in obese mice (Joung et al, ).…”
Section: Resultsmentioning
confidence: 99%